The thoracolumbar interfascial block with local anesthesia in osteoporotic vertebral compression fractures treated with percutaneous kyphoplasty provides better analgesia compared with local anesthesia alone: A randomized controlled study - Tao, Hong-lei; Zhang, Hang; Jiang, Yun-feng; Fan, Shan-shan; Wang, Hong-wei; Zheng, Ao-te (Frontiers in Surgery, 2023)
Objective To evaluate the safety and efficacy of the thoracolumbar interfascial block (TLIPB) in percutaneous kyphoplasty (PKP), and to confirm that the TLIPB further minimizes perioperative pain and residual back pain on the basis of local anesthesia. Method From April 2021 to May 2022, 60 patients with osteoporotic vertebral compression fractures were included in this prospective randomized controlled trial. Patients were randomly assigned to a local anesthesia group (A group) or a TLIPB on the basis of local anesthesia group (A + TLIPB group) before PKP. Pain level (visual analog scale, VAS), amount of analgesic rescue drugs (parecoxib), operative time, mean arterial pressure, heart rate, and complications were assessed and compared between the two groups. Results Compared with the A group, VAS scores were lower in the A + TLIPB group, respectively, when the trocar punctured the vertebral body (7.4 ± 0.7 vs. 4.5 ± 0.9; P < 0.01), during balloon dilatation (6.6 ± 0.9 vs. 4.6 ± 0.9; P < 0.01), during bone cement injection (6.3 ± 0.6 vs. 4.3 ± 0.8; P < 0.01), 1 h after surgery (3.5 ± 0.7 vs. 2.9 ± 0.7; P < 0.01), and 24 h after surgery (2.5 ± 0.8 vs. 1.9 ± 0.4; P < 0.01). Residual back pain (VAS: 1.9 ± 0.9 vs. 0.9 ± 0.8; P < 0.01) and the incidence of rescue analgesic use (P = 0.02) in the A + TLIPB group were lower compared with the A group. Compared with the A group, mean arterial pressure and heart rate were lower in the A + TLIPB group when the trocar punctured the vertebral body, and with balloon dilatation and bone cement injection; however, there were no statistical differences between the groups 1 and 24 h after surgery. The incidences of bone cement leakage, constipation, and nausea were similar between the two groups. No patient developed infection, neurological injuries, constipation in either group. Conclusion The addition of the TLIPB to local anesthesia can further minimize perioperative pain and residual back pain, and reduce perioperative rescue analgesic use. When added to local anesthesia, the TLIPB is an effective and safe anesthetic method for PKP. Clinical trial registration This study has been registered in the Clinical Trial registration: ChiCTR-2100044236.